DIAGNOSIS OF RUBELLA (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Rubella is an acute, contagious viral disease of significant public health importance due to its teratogenic effects and potential to cause congenital rubella syndrome (CRS). Although generally mild in children and adults, rubella infection during early pregnancy can result in severe fetal complications, including deafness, cataracts, cardiac defects, and neurodevelopmental disorders. Therefore, accurate diagnosis and effective prophylaxis remain critical components of disease control and elimination strategies.The diagnosis of rubella presents a challenge due to the nonspecific and often subclinical nature of its clinical manifestations. While the disease is classically associated with a low-grade fever, maculopapular rash, and lymphadenopathy, these symptoms overlap with other viral exanthems, necessitating laboratory confirmation. Serological methods, particularly the detection of rubella-specific IgM antibodies via enzyme-linked immunosorbent assay (ELISA), constitute the cornerstone of diagnosis. In addition, the identification of a significant rise in IgG antibody titers between paired serum samples provides evidence of recent infection. Molecular diagnostic techniques, such as reverse transcription polymerase chain reaction (RT-PCR), have enhanced the sensitivity and specificity of detection, especially in early stages of infection and in cases of congenital transmission. These methods allow for direct identification of viral RNA in clinical specimens, thereby supporting both clinical management and epidemiological surveillance.Prophylaxis of rubella is primarily achieved through active immunization, which has proven to be highly effective in reducing disease incidence and preventing outbreaks. The live attenuated rubella vaccine, commonly administered as part of the combined measles-mumps-rubella (MMR) vaccine, induces long-lasting immunity in the majority of recipients. Widespread vaccination programs have led to a dramatic decline in rubella cases in many regions; however, gaps in immunization coverage continue to pose risks for resurgence. Special emphasis is placed on the immunization of women of reproductive age, as this is the most effective strategy to prevent congenital rubella syndrome. Preconception screening for rubella immunity and timely vaccination of seronegative individuals are essential preventive measures.In addition to vaccination, public health interventions such as surveillance, outbreak response, and infection control practices play a vital role in limiting transmission. Isolation of infected individuals, adherence to respiratory hygiene, and monitoring of susceptible populations contribute to comprehensive disease control. Although passive immunization with immunoglobulin may be considered in certain high-risk situations, it does not replace vaccination as the primary preventive strategy.